India - Can Results-Based Incentives Encourage Teachers to Attend School? - Vivek, Kumar; Bhattacharjee, Pradyumna; Mani, Subha; Avinav, Kumar (World Bank, Washington, DC, 2021)
The Results in Education for All Children (REACH) Trust Fund supports and disseminates research on the impact of results-based financing on learning outcomes. The EVIDENCE series highlights REACH grants around the world to provide empirical evidence and operational lessons helpful in the design and implementation of successful performance-based programs. A REACH-supported study tested the impact of results-based incentives for meso-level officials (Resource Persons, or RPs) and teachers on teacher attendance at school. The incentives led to a 15 percentage point increase in the likelihood of a teacher being present, averaged across audit visits. The training increased the amount of time RPs spent mentoring teachers, but this increased mentoring did not lead to any changes in teaching practices.